Sosialisasi dan Pembinaan Pekarangan Pangan Lestari (P2L) Pada Kelompok Wanita Tani di Wilayah Kota Blitar - Serdani, Army Dita; Puspitorini, Palupi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The Ministry of Agriculture is promoting the Sustainable Food Program (P2L) which aims to meet people's needs for food and nutritional consumption patterns as well as ways to maximize empty land which can be used as an opportunity for conservation (Annonimous, 2021). Another aim is to increase community awareness and family knowledge about the processing and care of food plants, fruit and vegetables for cultivation, encourage the growth of seeds or plants so that their sustainability is maintained and increase the community's productive income by supplying and utilizing empty land in their respective home gardens. In the field, it is still difficult to implement P2L in the target group, namely the Women Farmers Group in the city of Blitar. For this reason, outreach and coaching activities are needed so that group understanding and awareness can increase enthusiasm in implementing it, so that it will increase the availability, accessibility and use of their yards as a source of food as well as collecting cash. Community organizations are involved in this organization. By utilizing the yard, the community is encouraged to grow food crops, vegetables, fruit, medicinal plants, tuber plants as an alternative for food diversification as part of the P2L program. More than that, the P2L program is an agricultural business in or around the city that utilizes knowledge, experience and creativity to cultivate and process food for the community by utilizing empty land and yards to contribute to nutrition, improve the local community's economy and improve welfare (Aini , 2015). P2L activities are carried out using sustainable agricultural development methods, utilization of local resources (local wisdom), community empowerment (community engagement), and marketing focus strategies to achieve these goals (go to market). The implementation is planting various plants through nursery work, demonstration plots, planting, post-harvest work and commercialization. (Musdalifah et al., 2023) The activity was carried out using a lecture method explaining the legality of P2L implementation, implementation, implementation procedures to 20 KWTs in the Blitar City Area by the proposer of Unisba Blitar Internal PKM 2024.